ARCESILAUS: SOCRATIC SKEPTICISM IN PLATO’S ACADEMY - Harald Thorsrud (Lexicon Philosophicum)
The fundamental issue regarding Arcesilaus’ skepticism is whether it should be understood as a philosophical position or as a strictly dialectical practice with no doctrinal content. In this paper I argue that it is both by providing an account of the epistemic principles informing his practice along with a positive doxastic attitude that he may consistently take towards those principles. I further show how Arcesilaus may have reasonably derived his Socratic project, including the epistemic principles and his distinctive cognitive attitude, from his reading of Plato’s dialogues, and that this approach enables us to better understand the function of his practical criterion, the reasonable (to eulogon). And finally, I note that since Arcesilaus’ great successor Carneades confronts the same problem regarding the coherence of his Socratic project, a similar interpretative approach may be taken to his practical criterion, the persuasive (to pithanon).